In Vitro Evaluation of the Effect of Abrasion on the Surface Roughness of Bulk Fill and Its Comparison with Conventional Composites - farnaz farahat; zahra moradi mazraeno; alireza daneshkazemi (Mashhad University of Medical Sciences, 2021)
Introduction: Surface properties are among the most important factors in clinical success of composite restorations. The composite surfaces may be affected by the occlusion forces, tooth brushing, or bacteria. This study aimed to evaluate the surface roughness of Bulk fill and universal nano-hybrid composites after toothbrush abrasion. Materials and Methods: Totally, nine specimens were prepared for each nano-hybrid composite (Tetric N Ceram and Tetric N Ceram Bulk fill) in this in vitro study. The surface roughness of the specimens was evaluated using a contact profilometer. Subsequently, the samples were abraded in a brushing machine using a soft toothbrush and slurry of toothpaste and distilled water at 10000 strokes. Following that, the mean surface roughness of the samples was measured again. Data were analyzed using one-way ANOVA, t-test, and paired-t-test. A p-value less than 0.05 was considered statistically significant. Results: After abrasion, surface roughness was increased in both types of composites. Moreover, the surface roughness of the TNC Bulk fill was significantly higher than that of the TNC composite. Conclusion:Due to the high surface roughness of the Bulk fill composite after abrasion, it is recommended to cover the surface of Bulk fill composites with a more abrasion resistant composite.